Effects of milling process parameters and PCAs on the synthesis of Al0.8Co0.5Cr1.5CuFeNi high entropy alloy powder by mechanical alloying. (May 2022) - Huang, Minjie; Jiang, Jufu; Wang, Ying; Liu, Yingze; Zhang, Ying
Graphical abstract: Highlights: The grain size decreased as rotational speed, milling time and ball to powder weight ratio increased, the change of lattice strain was opposite. The carbon and oxygen pollution levels introduced by stearic acid were higher than n-heptane and lower than ethanol. Severe cold-welding resulted in the formation of Fe, Cr, Ni rich regions. Concentration gradient sites were increased through refinement of particles and enrichment regions, accelerating dissolution and alloying. Abstract: Nine schemes were designed to study the effects of milling parameters (rotational speed, ball to powder weight ratio, milling time) and process control agents (PCAs) on the synthesis of Al0.8 Co0.5 Cr1.5 CuFeNi powders by mechanical alloying (MA). By using X-ray diffraction (XRD), the solid solutions formation during MA were studied, the grain size and lattice strain were calculated. The morphology, microstructure and composition of the powders were analyzed by scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS). The grain size decreased as rotational speed, milling time, ball to powder weight ratio increased, the change of lattice strain was opposite. The carbon and oxygen pollution levels introduced by stearic acid were higher than those introduced by n-heptane and lower than those introduced by ethanol. The powders were hardly alloyed when stearic acid was added at initial stage, but could be effectively alloyed after pre-alloying. Cold-welding was effectively inhibited and particles were greatly refined when 1 wt% ethanol and stearic acid were added respectively. Solid solutions formation was affected by cold-welding and fracture. Severe cold-welding led to Fe, Cr, Ni rich regions formation. Refinement of particles and enrichment regions resulted in the increase of concentration gradient sites, accelerating dissolution and alloying.